Plastic intensity reduction using thermally insulating coatings for injection molds. (August 2020) - Sorgato, Marco; Masato, Davide; Piccolo, Leonardo; Lucchetta, Giovanni
Graphical abstract: Highlights: Insulative mold surface coatings were characterized to allow the design of thinner plastic parts. DLC showed an outstanding effect on the reduction of melt flow resistance of PET, with a maximum pressure drop reduction of 25%. The value of the HTC in a numerical model was calibrated to the experimental pressure data. The calibrated model was used to quantify the potential thickness reduction of a case study. Using this coating it is possible to reduce the thickness and the volume of the part by 13% and 8% respectively. The thinner design positively affects the duration of the time cycle, reducing it by 22%. Abstract: The use of plastics in today's world is still increasing despite its enormous burden for environmental sustainability. The urge to reduce plastics impact is driving the development of novel technological solutions. The high viscosity of thermoplastic polymer melts often leads to the design of oversized plastic parts having wall thickness higher than structural requirements. This work proposes a novel approach to wall thickness reduction, exploiting the thermally insulating effect of mold coatings. Four different mold coatings were characterized using inline rheological testing carried out on a PET using a slit-die open mold. The thermal boundary condition of a numerical model was calibrated by fitting the numerical to experimental pressure values. The thickness reduction associated with the use of a specific coating was then quantified for a case study geometry using the calibrated model. The results indicated that it is possible to reduce the thickness of the part by 12%, leading to material consumption and cycle time reduction of 8% and 22%, respectively.